EFFECT OF MICROALGAE ON GROWTH AND FATTY ACID PROFILES OF HARPACTICOID COPEPOD, Tisbe holothuriae - Gede Suwarthama Sumiarsa; Philip Teguh Imanto (Indonesian Aquaculture Journal, 2009)
Growth of marine copepods is influenced by feed. The purposes of this trial were to observe both growth and fatty acid compositions of harpacticoid copepod nauplii, Tisbe holothuriae by feeding with several microalgal species in laboratory: (A) Isochrysis tahiti; (B) Nannochloropsis oculata; (C) Rhodomonas sp., and (D) Tetraselmis chuii. The trial was carried out for 35 days with randomized complete design and triplicates in each treatment. The results showed that final copepod nauplii densities were not significantly different (P>0.05) in all treatments. However, lipid content of copepod nauplii fed with T. chuii was significantly higher (P<0.05) compared to that of other treatments while fatty acid profiles of EPA, DHA and DHA/EPA ratios showed both insignificant and significant differences among treatments.